Gestão estratégica voltada para a exportação em micro e pequenas empresas fruticultoras - Campos, Teodoro Malta (2010)
The objective of this work is to study the strategic management of export-oriented in small business fruit growers, with special interest is checking the influence of the constructs of deliberate strategy of the emerging strategy and learning processes. The study uses the qualitative method through case study, so that four companies located in São Paulo are studied. The results showed that the export-oriented strategic management is strongly influenced by the constructs of deliberate strategy and emergent strategy of learning. The companies to be able to export had to promote changes in their internal structure, in order to overcome barriers to entry due to phytosanitary legislation. For this, the four companies passed through the process of obtaining certification Globalgap, which serve as a seal recognized by the international market, which serves to overcome barriers to entry. Of the four companies in the sample, three were successful in obtaining Globalgap. The owner-manager motivation for export was identified as a factor affecting the success to obtain certification. The results also showed that the strategic management of export-oriented strategy is based in deliberate and emergent strategy the two coexisting simultaneously. The deliberate strategy was found in the management of internal activities of the properties through the development of rational processes of control of fruit to achieve the quality standards demanded by the international market. The emerging strategy is linked to the development of knowledge about the functioning of the international export of fruit. It was also possible to observe the learning processes that accured through the acquisition of new knowledge that led to changes in the structure of the companies studied.